2017
DOI: 10.2147/oarrr.s128675
|View full text |Cite
|
Sign up to set email alerts
|

Single-arm open-label study of Durolane (NASHA nonanimal hyaluronic acid) for the treatment of osteoarthritis of the thumb

Abstract: IntroductionOsteoarthritis of the trapeziometacarpal (TMC) joint of the thumb – also known as rhizarthrosis – is painful and has a significant impact on quality of life. Intra-articular injection of hyaluronic acid may potentially meet the need for effective, minimally invasive intervention in patients not responding adequately to initial treatment. We aimed to confirm the safety and effectiveness of viscosupplementation with Durolane (NASHA nonanimal hyaluronic acid) in rhizarthrosis.Patients and methodsThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
(17 reference statements)
1
15
0
1
Order By: Relevance
“…Biomedical B Baumann Group [242] 10 × 10 12 Da NASHA HAs Durolane Bioventus (USA) [243,257,268,269] functionalities which are reactive with bi-functional reagents and these can be used to attach peptides to the CS backbone. AFM confirmed that the attached peptides adopted a bristle-like distribution in a bottle-brush type arrangement on the CS core and they thus explored all available spatial orientations which would be expected to optimize the space-filling and interactive properties of the peptidoglycans.…”
Section: Features Of Peptidoglycan Neo-aggrecan and Lubricin Mimetic Pgsmentioning
confidence: 99%
“…Biomedical B Baumann Group [242] 10 × 10 12 Da NASHA HAs Durolane Bioventus (USA) [243,257,268,269] functionalities which are reactive with bi-functional reagents and these can be used to attach peptides to the CS backbone. AFM confirmed that the attached peptides adopted a bristle-like distribution in a bottle-brush type arrangement on the CS core and they thus explored all available spatial orientations which would be expected to optimize the space-filling and interactive properties of the peptidoglycans.…”
Section: Features Of Peptidoglycan Neo-aggrecan and Lubricin Mimetic Pgsmentioning
confidence: 99%
“…In this paper, because the research is mainly about the basic movements of the hand, we choose the forearm which is closer to the hand distance to extract the signal. In practice, the fingers of the hand can be divided into three parts according to the motion correlation degree, that is, the distribution of the thumb and the index finger as a single motion part and the other three fingers together to form a motion part; Kapandji test ,which is a widely used evaluation criterion for the dexterity of the prostheses in the world [20][21][22]. The core of the standard is whether the thumb of the bionic hand can touch the fingertips and of the other four fingers conveniently.…”
Section: Acquisition Of Surface Electromyography Signalmentioning
confidence: 99%
“…The support vector machine is mainly used for multi classification, the kernel function type is RBF (radial basis) kernel function, the kernel function parameter is 3.05176*10-5, the total number of classes is 9, the whole SVM model support vector number is 278, the support vector of each category is numbered. Instead of 37,32,14,21,26,37,30,42 and 39, the model will list all the support vectors.…”
Section: Establishment Of Support Vector Machine Classification Modelmentioning
confidence: 99%
“…Musculoskeletal hand problems, like osteoarthritis, can cause pain, significant impairment of daily activities and reduced satisfaction with hand appearance . Future research on the consequences of hand bleeds should be performed.…”
Section: Discussionmentioning
confidence: 99%